A novel concept of cost-effective active debris removal spacecraft system. Issue 3 (September 2020) - Okamoto, Hiroyuki; Yamamoto, Toru
Abstract: Post Mission Disposal (PMD) alone is an insufficient solution to stabilize the orbital debris environment, but combining Active Debris Removal (ADR) with PMD and other means of debris mitigation is considered a promising remediation method. The cost reduction of ADR is essential to make it a sustainable business. The major cost driver of ADR is the ADR spacecraft and its launcher, both of which are largely influenced by the spacecraft size. A trade-off study of the ADR spacecraft system has been conducted to minimize its size, resulting in the novel concept of a cost-effective ADR spacecraft system. The authors introduce the combination of electric propulsion (EP) and air drag utilization for the debris deorbit phase so as to lower the EP requirement, thereby leading to cost reduction of the ADR spacecraft. The minimum delta-V reentry method is also considered to reduce the propellant mass for final reentry. EP performance (e.g. thrust, specific impulse, mass) is modeled as a function of power consumption, and optimum EP performance has been explored to minimize overall mass of the ADR spacecraft, including its electrical power subsystem with this EP model. Given the minimum thrust limit to satisfy the mission duration requirement, a higher thrust-to-power ratio is preferable for debris removal electric propulsion. This paper discusses the optimal EP performance requirements in detail, and the results show that a roughly 500-kg ADR satellite using a 600-W-class Hall thruster can remove about three tons of a rocket body debris from an 800-km circular orbit within 600 days.